Towards a common definition of global health - Sewankambo, K .Nelson (Lancet, 2009)
Global health is fashionable. It provokes a great deal of media, student, and faculty interest, has driven the establishment or restructuring of several academic programmes, is supported by governments as a crucial component of foreign policy, 1 and has become a major philanthropic target. Global health is derived from public health and international health, which, in turn, evolved from hygiene and tropical medicine. However, although frequently referenced, global health is rarely defined. When it is, the definition varies greatly and is often little more than a rephrasing of a common definition of public health or a politically correct updating of international health. Therefore, how should global health be defined?
Keywords: Global health; Public health; Hygiene and tropical medicine